Dampak Sosialisasi Bullying pada Siswa SMP dan Penguatan Pendidikan Karakter Remaja - Nurida Wita; Gustina Erlianti; Machaby Khalifa Fajrin; Fuadil Fikri; Hefri Gusnadi; Muhammad Fayyadhiman Willyarto (CV. ITTC INDONESIA, 2026)
Bullying is one of the most serious problems among adolescents in Indonesia, particularly in junior high school environments. This study aims to analyze the impact of bullying socialization on junior high school students and its influence on character education strengthening among adolescents. This research uses a qualitative approach with a literature study method. Data were collected from scientific articles and journals published between 2017–2024 indexed in SINTA and Google Scholar. The results show that bullying in junior high schools manifests in physical, verbal, social, and cyberbullying forms. The socialization of anti-bullying programs has proven effective in increasing students’ awareness of the negative impacts of bullying. Strengthening character education through religious values, integration in learning activities, school culture programs, and anti-bullying socialization has contributed significantly to reducing bullying behavior and forming adolescents with positive character. Collaboration between schools, teachers, and parents plays a crucial role in creating a safe and supportive learning environment.